2013
DOI: 10.4236/pp.2013.49092
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir Renal Toxicity: Evaluation of Cohorts and Clinical Studies—Part One

Abstract: Tenofovir is one of the most commonly used antiretrovirals in adolescents and adults because of its potency and favorable pharmacokinetic and relative safety toxicological profile. It has been combined successfully with antiretroviral drugs from classes such as protease inhibitors, non-nucleoside reverse transcriptase inhibitors and nucleoside reverse transcriptase inhibitors to achieve virologic suppression in a high percentage of recipients. Despite its therapeutic success, quite a number of cohorts and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“… 2 , 3 In many studies, treatment with TDF was associated with kidney tubular dysfunction and reduced renal function, with higher prevalence being associated with female gender and age between 40 and 50 years. 4 , 5 , 6 The main target of toxicity is the proximal renal tubule, and in severe cases patients developed renal Fanconi syndrome. 7 Studies have shown that albuminuria might be a more reliable marker for glomerular and proximal tubular dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 3 In many studies, treatment with TDF was associated with kidney tubular dysfunction and reduced renal function, with higher prevalence being associated with female gender and age between 40 and 50 years. 4 , 5 , 6 The main target of toxicity is the proximal renal tubule, and in severe cases patients developed renal Fanconi syndrome. 7 Studies have shown that albuminuria might be a more reliable marker for glomerular and proximal tubular dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“… 8 The effect of TFV on glomerular function is less severe than renal tubular function. 6 TFV nephrotoxicity leads to break down of solute transport characterised by urine wasting of solutes and proteins such as albumin normally reabsorbed in the proximal tubule. 7 Genetic polymorphisms in proximal tubule transporters may predispose certain individuals to accumulate high intracellular TFV levels and could increase the risk of developing proximal tubular toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Lopinavir is usually boosted with ritonavir to increase its pharmacological profile. In the management of HIV/AIDS lopinavir/ritonavir is used as a combination therapy with other antiretroviral drugs [12,13,14,15]. Lopinavir/ritonavir mediates its antiviral activity by binding the protease enzyme, and preventing the cleavage of the gag and gag/pol polyproteins into structural functional proteins and enzymes thereby preventing the formation of new viral particles [16].…”
Section: Introductionmentioning
confidence: 99%
“…Since its approval by the US Food and Drug Administration (FDA) in 2001, tenofovir disoproxil fumarate (TDF) has been in clinical use as treatment for HIV-1 infection in combination with other antiretroviral (ARV) drugs, pre-exposure prophylaxis (PrEP) for prevention of sexually acquired HIV-1 infection, and treatment of chronic hepatitis B virus (HBV) infection [ 1 , 2 ]. Because TDF has a favorable potency, tolerability, and pharmacokinetic profile that allows for daily dosing, it is one of the most commonly used ARVs in adolescents and adults [ 3 ].…”
Section: Introductionmentioning
confidence: 99%